Analisis Confirmatory Factor Analysis (CFA) Konstruk Student Engagement Pada Mahasiswa Universitas Negeri Padang - Mentari, Findia; Yulhendri, Yulhendri (Universitas Batanghari Jambi, 2026)
This study aims to analyze the construct factors of student engagement in Padang State University students using the Confirmatory Factor Analysis (CFA) approach. Using a quantitative approach with a research sample of 395 undergraduate and diploma students from various faculties selected through proportionate stratified random sampling, data were collected with a questionnaire using a Likert scale and analyzed with SEM-PLS and AMOS. The results show that overall student engagement reached a TCR of 76.95 (good category), then the cognitive dimension (TCR 76.93), emotional (76.43), and behavioral (78.02), which indicates that all indicators are valid (loading factor > 0.5), composite reliability 0.913 (> 0.70), and goodness of fit is good (RMSEA 0.113; CFI 0.981). This study contributes to the development of valid and reliable student engagement measurement instruments in a higher education context at UNP.